A world in your ear - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
You know that saying about how the pictures are always better on the radio? Well, you might want to know about Spore's big sister on the radio, a sort of Spore-of-the- airwaves, the Rural Radio Resource Packs (RRRP) programme which is now entering...